The Influence of the Use of Audio-Visual Media in Improving Speaking and Listening Skills - Islamiyah, Mubarokatul; Hamzah, Amir; Maryana, Tatik (Indonesian Journal of Educational Studies, 2025)
Abstract. Speaking and listening skills are essential aspects of language learning. However, in practice, seventh-grade students at SMP Negeri 2 Torjun Sampang have difficulty in both skills. This study aims to investigate the impact of audio-visual media on enhancing students' speaking and listening skills. This study used a mixed-methods approach with a quasi-experimental one-group pretest-posttest design. The study subjects were 27 students from class VII-C (the control class) and 26 students from class VII-B (the experimental class), selected using purposive sampling. Data collection techniques were carried out through questionnaires, observations, and interviews. Quantitative data analysis used the t-test, and qualitative data analysis through the reduction and interpretation of interview and observation results. The results showed a significant improvement in students' speaking and listening skills after learning with audio-visual media, specifically animated videos. The average post-test score increased compared to the pre-test, and students demonstrated greater activity and motivation during the learning process. Thus, the alternative hypothesis (H₁) is accepted, which states that audio-visual media has a significant effect on improving the speaking and listening skills of class VII students at SMP Negeri 2 Torjun Sampang.  Keywords: Audio-Visual Media, Speaking Skills, and Listening Skills